How community participation and stakeholder involvement can improve recycling : an investigation of initiatives and opportunities in Simunye - Myeni, Jabu R (Rhodes University, Faculty of Commerce, Rhodes Business School, 2013)
This report presents the findings of a research project whereby the initiatives and opportunities for municipal solid waste (MSW) recycling were investigated in the town of Simunye, in Swaziland with a view to establish how recycling, in particular household waste recycling, can be improved through stakeholder involvement and community participation during the planning and implementation of a sustainable system for household waste recycling in Simunye. The reason for focusing on household waste was because source separation of household waste was identified as a potential area for improving efficiencies and cutting costs by the local authority. It was deemed necessary to conduct research because there was a history of failure in respect of household recycling. In 2006 an initiative, by the local authority, for separating household waste at source had ended up in failure. The participation rates of the households turned out to be very low even though they had been issued, free of charge, some plastic bags for sorting the waste. Some of the households were found using the bags for other purposes rather than recycling. As a result, the initiative had to be suspended (White, 2010). There is a new move to revive the project in order to cut costs and minimize wastages. This time around the local authority is determined for the new project to be a success story. Since the underlying causes for the failure of the previous initiative were never investigated formally (Khumalo, 2010), the starting point would be to identify and try to eliminate all the potential barriers to recycling through a consultative process to start with.
Keywords: Recycling (Waste, etc.) -- Swaziland; Refuse and refuse disposal -- Swaziland -- Citizen participation